Analisis Metode Dakwah dalam Perspektif Pemberdayaan - Asrul Harahap; Masrul Efendi Umar Harahap (Jurnal at-Taghyir: Jurnal Dakwah dan Pengembangan Masyarakat Desa, 2022)
The use of methods is very important in obtaining the success of any process, the better the method used, the more effective the process is in achieving the desired goal. In da'wah activities, method is important to achieve the goals of da'wah. Talking about the da'wah method, it is very identical to the da'wah method in surah an-nahl verse 125, namely the method of bil hikmah, mau’izhah and Mujadalah. If we examine this da'wah method in the perspective of empowerment, it will be found a match between the da'wah method in Surah an-nahl verse 125 with the empowerment method in general. Da'wah with empowerment has similarities in its activities, they both carry out the process of releasing themselves for the community or their mad'u from bad conditions to better conditions, and in the end they become independent and able to overcome their problems independently.